Causal Relationship Between Air Pollutants and Blood Pressure Phenotypes: A Mendelian Randomization Study - Xianshang Zhu; Huabo Mao; Hongyu Zeng; Fengli Lv; Jiancheng Wang (Global Heart)
Objectives: Hypertension is a chronic disease widely prevalent around the world. While previous observational studies have suggested a link between air pollutants and an increased risk of hypertension, causality has not been established. Our study aimed to investigate potential causal relationships between five air pollutants and four blood pressure phenotypes through two-sample Mendelian randomization. Methods: Two-sample Mendelian randomization (MR) analyses were performed using genome-wide association studies (GWAS) data from the IEU OpenGWAS project. The main analysis method was the inverse variance weighting (IVW) method. Heterogeneity was assessed by Cochran’s Q test, while pleiotropy was assessed by MR-Egger regression. Sensitivity analysis was performed by weighted median method, MR-Egger method, simple mode method, weighted mode method, and leave-one-out analysis method. Results: Mendelian randomization results showed positive causal associations between PM10 with hypertension (OR: 1.49; 95%CI: 1.06, 2.09; P: 2.23 × 10–2) and systolic blood pressure (β: 1.89; 95%CI: 0.32, 3.47; P: 1.85 × 10–2), positive causal associations between PM2.5 and hypertension (OR: 1.26; 95%CI: 1.01, 2.58; P: 4.30 × 10–2), and negative causal ibetween NO2 and systolic blood pressure (β: –1.71; 95%CI: –3.39, –0.02; P: 4.74 × 10–2). None of the above associations were subject to pleiotropic bias, and all associations were heterogeneous except for PM10 and hypertension. The leave-one-out analysis showed that no single SNP affected the stability of the results. Conclusion: Elevated levels of PM2.5 and PM10 have been associated with an increased risk of developing hypertension, with PM10 specifically linked to higher systolic blood pressure levels. Interestingly, NO2 has shown potential as a protective factor in lowering systolic blood pressure. This study clarifies the causal relationship between five air pollutants and elevated blood pressure. Ensuring good ambient air quality is essential in preventing hypertension and reducing the overall disease burden.